Into the clinic: Talimogene laherparepvec (T-VEC), a first-in-class intratumoral oncolytic viral therapy - Ann W. Silk; Howard L. Kaufman; Hasan Rehman; Michael P. Kane (Journal for ImmunoTherapy of Cancer)
With the recent regulatory approval of Talimogene laherparepvec (T-VEC) for the treatment of advanced of melanoma in the United States, Europe and Australia, oncolytic virus immunotherapy has earned its place in the clinic. However, the adoption of T-VEC by the U.S. oncology community has been slow, and so far has been largely limited to specialized cancer centers. Limiting factors include the intratumoral route of administration, which is unfamiliar to medical oncologists, biosafety concerns related to the use of a live virus in the clinic, and the explosion of other therapeutic strategies now available for the treatment of advanced melanoma. Herein, we review the development of T-VEC, and suggest how it fits into the in the current clinical treatment paradigm, and provide pearls for drug preparation, administration, and monitoring of response to therapy.